Cognitive Correlates of Math Performance in School-Aged Children with Sickle Cell Disease and Silent Cerebral Infarcts. (4th September 2020) - Peterson, Rachel K; Williams, Suzan; Janzen, Laura
Abstract: Objective: Attention, processing speed, executive functioning, and math difficulties are common in youth with sickle cell disease (SCD) with silent cerebral infarcts (SCI). This study investigated the cognitive underpinnings of math difficulties in children with SCD and SCI. Method: Youth ( n  = 68) with SCD and SCI completed measures of attention [Digit Span forward (DSF); Conners Continuous Performance Test-Third Edition/Kiddie Conners Continuous Performance Test-Second Edition (CPT-3/KCPT-2)]; working memory [Wechsler Intelligence Scales (WPPSI-IV, WISC-IV, WISC-V, WAIS-IV), Working Memory Index (WMI), Digit Span backwards (DSB)]; processing speed [WPPSI-IV, WISC-IV, WISC-V, WAIS-IV Processing Speed Index (PSI)]; math reasoning [Wechsler Individual Achievement Test-Third Edition (WIAT-III) Mathematics composite (MC)]; and math fluency [WIAT-III Math Fluency composite (MF)] as part of a clinical neuropsychological evaluation. Parent ratings of attention and executive functioning were obtained [Behavior Assessment System for Children-Third Edition (BASC-3), Behavior Rating Inventory of Executive Function (BRIEF)]. Results: MC was positively correlated with WMI ( r  = 0.59, p  = 0.00), PSI ( r  = 0.40, p  < 0.001), DSF ( r  = 0.29, p  = 0.03), DSB ( r  = 0.47, p  < 0.001), and MF ( r  = 0.71, p  < 0.001). Correlations between MC, sustained attention, and parent ratings were nonsignificant. The linear regression model using correlated variables was significant [F(4, 51) = 8.29, R 2  = 0.39, p  < 0.001]. WMI was the only significant variable within the model ( p  = 0.02). Conclusions: Working memory deficits account for significant variance in untimed mathematical performance in this population—consistent with other populations with white matter dysfunction. Interventions targeting both mathematics and working memory may be beneficial.